Analisis Perkiraan TDOA menggunakan Algoritma LMS Adaptif pada Pelacakan Paus Lodan - Andriyan Permana; Agfianto Eko Putra; Catur Atmaji (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2015)
Research on TDOA estimation in sperm whale tracking has been done [1] that uses the Teager - Kaiser operator in improving accuracy the TDOA estimation using adaptive LMS algorithm on sperm whale tracking. However, further researches on the right convergence factor (μ) (fast and accurate) in TDOA estimation using adaptive LMS algorithms for sperm whale tracking have not been performed. Will be analyzed the TDOA estimation using adaptive LMS algorithm in sperm whale tracking with the variation of μ. As a reference to determine the right value of μ, the results of sperm whale tracking[2] is used.TDOA estimation using Adaptive LMS algorithm was first published by Benesty [3]. The approach taken is based on estimation of the impulse responses from source to receivers. In the adaptive LMS algorithm function updates the coefficient with μ as adaptation step. TDOA values obtained from the difference between the two impulse responses.From the results, values changing of μ affect the speed of TDOA estimation using the LMS adaptive algorithm. However, the wrong value of μ is lead to inaccurate sperm whale tracking results. The best value of μ for TDOA estimation using the LMS adaptive algorithm for sperm whale tracking is 0.01.